The dynamics of social practice everyday life and how it changes - Shove, Elizabeth 1959-; Pantzar, Mika; Watson, Matt; SAGE Knowledge (Online service). (Los Angeles, California Sage Publications, 2012)
Everyday life is defined and characterized by the rise, transformation and fall of social practices. Using terminology that is both accessible and sophisticated, this book guides the reader through a multi-level analysis of this dynamic. The book provides discussion of real world examples such as the history of car driving and the emergence of frozen food, bringing abstract concepts to life and grounding them in empirical case-studies and new research. Demonstrating the relevance of social theory for public policy problems, the authors show that the everyday is the basis of social transformation.
The dynamics of social practice -- Introducing theories of practice -- Materials and resources -- Sequence and structure -- Making and breaking links -- Material, competence and meaning -- Car-driving: elements and linkages making links - Breaking links -- Elements between practices -- Standardization and diversity -- Individual and collective careers -- The life of elements -- Modes of circulation -- Transportation and access: material -- Abstraction, reversal and migration: competence -- Association and classification: meaning -- Packing and unpacking -- Emergence, disappearance and persistence -- Recruitment, defection and reproduction -- First encounters: networks and communities -- Capture and commitment: careers and carriers -- Collapse and transformation: the dynamics of defection -- Daily paths, life paths and dominant projects -- Connections between practices -- Bundles and complexes -- Collaboration and competition -- Selection and integration -- Coordinating daily life -- Circuits of reproduction -- Monitoring practices-as-performances -- Monitoring practices-as-entities -- Cross-referencing practices-as-performances -- Cross-referencing practices-as-entities -- Aggregation -- Elements of coordination -- Intersecting circuits -- Representing the dynamics of social practice -- Representing elements and practices -- Characterizing circulation -- Competition, transformation and convergence -- Reproducing elements, practices and relations between them -- Time and practice -- Space and practice -- Dominant projects and power -- Promoting transitions in practice -- Climate change and behaviour change -- Basis of action -- Processes of change -- Positioning policy -- Transferable lessons -- Practice theory and climate change policy -- Configuring elements of practice -- Configuring relations between practices -- Configuring careers: carriers and practices -- Configuring connections -- Practice oriented policy making.
Keywords: Social change; Social sciences -- Philosophy; Social policy